Pengaruh Kualitas Audit, Ukuran Perusahaan Dan Leverage Terhadap Manajemen Laba Pada Perusahaan Perbankan Yang Tercatat Di Bursa Efek Indonesia Tahun 2016-2018 - Rodhiya Maulidah; Rahmat Agus Santoso (Universitas Muhammadiyah Gresik, 2020)
The existence of earnings information that is needed in the financial statements can be targeted by parties who are not responsible for carrying out earnings management practices. There are several factors that can present earnings management practices, namely audit quality, company size and leverage. This study discusses the evaluation of quality, company size and leverage on earnings management in banking companies listed on the Indonesia Stock Exchange in 2016-2018. By using 117 samples of annual financial statements or financial statements of companies listed on the Indonesia Stock Exchange. Tests carried out using multiple linear regression. Regression results indicate the results of quality audits and firm size significantly influence earnings management. Meanwhile, leverage is not significant to earnings management. It is expected that the results of this study can add insight for users of financial statements to pay attention to audit quality and company size to avoid earnings management practices.